Perceived Risk and Purchase Intention of Fashion Products Through Social Media Platforms in Makassar City - Abdul Karim; Amrullah Ahmad; Hardianto Hawing (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study analyzes the relationship between risk perception and the purchase intention of fashion products through social media platforms in makassar city. Risk perception includes dimensions of financial risk, security risk, privacy risk, and product risk, which can affect consumer interest in purchasing. This study uses a quantitative method with a survey technique through a questionnaire distributed to 99 respondents who are active users of social media in makassar city. The data analysis technique used is multiple linear regression to test the effect of risk perception on purchase intention. The study results indicate that risk perception significantly affects the purchase intention of fashion products through social media. Security and privacy risks have the most significant negative influence, while financial risk has a lower impact. Innovative marketing strategies, such as influencers and positive consumer reviews, have been shown to reduce risk perception and increase purchase intention. This study concludes that risk perception is an important factor that business actors must consider when marketing fashion products through social media platforms. It recommends increasing consumer trust through information transparency, secure payment systems, and credible consumer testimonials. This study contributes to understanding consumer behavior in the digital era, especially regarding online purchasing in makassar city.